Work function and negative electron affinity of ultrathin barium fluoride films. (1st July 2020) - Mezzi, Alessio; Bolli, Eleonora; Kaciulis, Saulius; Mastellone, Matteo; Girolami, Marco; Serpente, Valerio; Bellucci, Alessandro; Carducci, Riccardo; Polini, Riccardo; Trucchi, Daniele M.
Abstract : Thin films of barium fluorides with different thicknesses were deposited on GaAs substrate by electron beam evaporation. The aim of the work was to identify the best growth conditions for the production of coatings with a low work function suitable for the anode of hybrid thermionic‐photovoltaic (TIPV) devices. The chemical composition and work function φ of the films with different thicknesses were investigated by X‐ray photoelectron spectroscopy (XPS) and ultraviolet photoelectron spectroscopy (UPS). The lowest value of φ = 2.1 eV was obtained for the film with a thickness of 2 nm. In the valence band spectra of the films at low kinetic energy, near the cutoff, a characteristic peak of negative electron affinity was present. This effect contributed to a further reduction of the film's work function.